Understanding Web 3.0 - the Semantic Web : how the evolution to a third generation of the Web will impact upon the Internet and media environment within a global and South African context - Chetty, Lee-Roy (Centre for Film and Media Studies, 2014)
Includes bibliographical references (leaves 158-174).